2015
DOI: 10.1002/2015gc005937
|View full text |Cite
|
Sign up to set email alerts
|

Variations of the lithospheric strength and elastic thickness in North America

Abstract: We evaluate the effect of temperature variations on strength and effective elastic thickness (T e ) of the lithosphere of the North American (NA) continent. To this purpose, we use two thermal models that are corrected for compositional variations and anelasticity effects in the upper mantle. These thermal models are obtained from a joint inversion of gravity data and two recent seismic tomography models (NA07 and SL2013sv). The crustal rheology was defined using NACr14, the most recent NA crustal model. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
57
0
14

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(80 citation statements)
references
References 99 publications
(244 reference statements)
9
57
0
14
Order By: Relevance
“…The area in north-central Greenland toward the Nares Strait and Ellesmere Island has high T e (∼60-70 km; Figure 2a) and a shallow Moho (∼30 km; Figure 1d). An increased T e for the northern part of Ellesmere Island is also observed by Tesauro et al (2015). An increased T e for the northern part of Ellesmere Island is also observed by Tesauro et al (2015).…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…The area in north-central Greenland toward the Nares Strait and Ellesmere Island has high T e (∼60-70 km; Figure 2a) and a shallow Moho (∼30 km; Figure 1d). An increased T e for the northern part of Ellesmere Island is also observed by Tesauro et al (2015). An increased T e for the northern part of Ellesmere Island is also observed by Tesauro et al (2015).…”
Section: Resultsmentioning
confidence: 76%
“…The low T e values indicate that this area is the remnant of the failed Atlantic mid-ocean ridge in the Baffin Bay. Kirby and Swain (2009) and Tesauro et al (2015) have observed a similar feature, suggesting that the southern part of the Greenland craton is connected to the cratons of Eastern Canada. Kirby and Swain (2009) and Tesauro et al (2015) have observed a similar feature, suggesting that the southern part of the Greenland craton is connected to the cratons of Eastern Canada.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…However, edge-driven convection alone would produce low-velocity anomalies along the entire Laurentian margin. The lithosphere beneath the Appalachian orogeny appears to be relatively weaker in comparison with the cratonic lithosphere (Tesauro et al, 2015), making lithosphere erosion possible beneath the New England region. In addition, Figure 3b shows that the upper limit of the SNE-ENY anomaly is at the depth of 70 km, which is shallower than the average depth (~90-110 km) of the lithosphere-asthenosphere boundary beneath the Appalachians Rychert et al, 2005Rychert et al, , 2007.…”
Section: Discussionmentioning
confidence: 99%
“…9 (profile 2) that this area corresponds to a dense and likely strong mantle lithosphere extending to the bottom of the crust. It has been demonstrated that seismicity occurs at the boundaries of rigid lithospheric blocks in similar situations (Tesauro et al, 2015). In the case of the Nile Delta, the weak crust easily accommodates relatively small deformations, which in contrast to the Red Sea are limited by the strong lithosphere beneath.…”
Section: Fragmentation Of the Lithosphere In Egypt Based On Its Densimentioning
confidence: 99%